Social attitudes and regional inequalities - Vinko Muštra; Lena Malešević Perović; Silvia Golem (European Regional Science Association (ERSA), 2013)
The global economic crisis has had a major impact on the economies of EU Member States, among other things, public sector budget deficits and public debt levels have risen dramatically. This has been reflected also on the budgets of the European Union (EU) that had become tighter and raise the questions about the effectiveness of the EU?s expenditure, especially the most important parts such as Cohesion policy. The aim of this paper is to examine does the presence of social attitudes may influence the effectiveness of EU budget expenditure measured by the level of regional inequalities. The motivation is in the fact that individuals choose actions according to social attitudes, so it seems appropriate to test does the social attitudes, defined as our views of the others as a collective, create a difference, among other, in response to EU?s budget expenditure. The analysis starts by focusing on individuals? attitudes towards income from their own effort, and income which is derived from other people?s effort taking in mind that individual actions depends on their attitudes. In case that selfish individuals, preferring income derived from other people?s effort (?unearned income?), are the dominant group, higher level of ?unearned? income from redistributive policies will decrease effort and therefore decrease employment rate and growth rate in the specific area. Consequently it implies weaker positive effects of public expenditure and increasing regional inequalities. To test the hypothesis for EU budget expenditure the authors establish the link between a income from other people?s effort with the re-distributive dimension of the EU budget. Considering the different attitudes among the individuals in EU it is expected to lead to significant differences in effectiveness of this redistributive policy among European regions and consequently diverse regional inequalities. Empirical part research has involved data for 27 EU countries observed over two waves of European Value Surveys: 1999-2000 (Wave 1) and 2008-2009 (Wave 2). The results indicate the significant role of social attitudes for regional inequalities. More precisely, considering the fact that the higher values social attitudes variable represents higher share of ?socially minded? individuals, the results indicate that society with less ?selfish? individuals have lower levels of regional inequalities. Taking into account that EU includes countries with different social attitudes it raises the question is the simplification and uniform regional policy instruments appropriate answer for the regional problems in EU.
Keywords: 330; social attitudes; regional inequalities; EU budget expenditure